2023
DOI: 10.1007/s11011-023-01254-y
|View full text |Cite
|
Sign up to set email alerts
|

New insights on the potential effect of vinpocetine in Parkinson’s disease: one of the neglected warden and baffling topics

Abstract: Vinpocetine (VPN) is an ethyl apovincaminate that has anti-inflammatory and antioxidant effects by inhibiting the expression of nuclear factor kappa B (NF-κB) and phosphodiesterase enzyme 1 (PDE-1). VPN is used in the management of stroke, dementia, and other neurodegenerative brain diseases. VPN may be effective in treating Parkinson’s disease (PD). Therefore, this review aimed to clarify the mechanistic role of VPN in the management of PD. VPN has protective and restorative effects against neuronal injury by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The mechanism of α‐synuclein‐induced neurodegeneration is not well understood. However, the formation of neurotoxic α‐synuclein filaments might be the possible mechanism 126 . It has been shown that epilepsy and neurodegenerative diseases such as AD and PD share a frequent underlying mechanism 127 .…”
Section: The Mechanistic Role Of Metformin In Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of α‐synuclein‐induced neurodegeneration is not well understood. However, the formation of neurotoxic α‐synuclein filaments might be the possible mechanism 126 . It has been shown that epilepsy and neurodegenerative diseases such as AD and PD share a frequent underlying mechanism 127 .…”
Section: The Mechanistic Role Of Metformin In Epilepsymentioning
confidence: 99%
“…However, the formation of neurotoxic α‐synuclein filaments might be the possible mechanism. 126 It has been shown that epilepsy and neurodegenerative diseases such as AD and PD share a frequent underlying mechanism. 127 Released α‐synuclein from injured neurons activates astrocytes and microglia leading to neuroinflammation and degeneration of inhibitory neurotransmitters with subsequent induction of epileptogenesis.…”
Section: The Mechanistic Role Of Metformin In Epilepsymentioning
confidence: 99%
“…Besides, the activated microglia triggers the activation of astrocytes which also promote the expression and the release of pro‐inflammatory cytokines. 13 , 14 Mutated Parkin, PINK1 and DJ‐1 genes that induce mitochondrial dysfunction together with mutant α‐Syn and the extracellular neuromelanin from damaged dopaminergic neurons contribute in the activation of microglia and the development of neurodegeneration in the SN, 12 , 13 , 15 , 16 , 17 (Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%